Self-enforcing international environmental agreements and trade: Taxes versus caps - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2014)
This paper studies within a multi-country model with international trade the stability of international environmental agreements (IEAs) when countries regulate carbon emissions either by taxes or caps. Regardless of whether coalitions play Nash or are Stackelberg leaders the principal message is that the choice of caps or taxes matters. International trade and tax regulation are necessary conditions for the existence of the encompassing self-enforcing IEA, and that the latter is attained the more likely, the less severe the cli- mate damage. Hence, cap regulation is inferior to tax regulation insofar as in case of the former there exist no large and effective self-enforcing IEAs, in particular not the encompassing self-enforcing IEA. Further results are that for the formation of encompassing self-enforcing IEAs it does not matter whether climate coalitions play Nash or are Stackelberg leaders or whether fossil fuel is modeled as a consumer good or an intermediate good.
Keywords: C72; F02; Q50; Q58; 330; cap; tax; international trade; self-enforcing environmental agreements; Nash; Stackelberg